Techniques for Assessing Disciplined Attitudes of Santri in Arabic Subjects at Al-Irsyad Tengaran 7, Batu City - Shafrul Fajri; Nur Qomari (Kitaba, 2023)
This research intended to find out: 1) indicators of disciplinary attitude assessment, 2) assessment techniques discipline attitude at Al-Irsyad Tengaran Islamic Boarding School 7 Batu City, 3) efforts in instilling the values of discipline to the students at Al-Irsyad Tengaran Islamic Boarding School 7 Batu City. This study uses a qualitative approach with descriptive qualitative research methods. The data sources used by researchers in this study were school principals, heads of curriculum sections, Arabic subject teachers and students at Al-Irsyad Tengaran Islamic Boarding School 7 Batu City. The research results are: 1). There are 10 indicators for discipline attitudes assessment, 2) the assessment technique is carried out by the teacher for each subject in each note, but based on predetermined indicators. 3) inculcating the value of discipline including; a) the teacher and the pesantren always invite and guide the students to be on time, b) the teacher and the pesantren always invite the students to always maintain good and polite speech, c) the teacher and the pesantren also always appeal to all the students to can maintain neatness, especially in dressing, d) teachers in class has an obligation to the students to provide motivation and advice related to the importance of instilling discipline in carrying out activities